Using Simulation Tools to Model Renewable Resources The Case of the Thai Rubber Industry - Chanchaichujit, Janya (Springer International Publishing, 2018)
This book provides a detailed study of the Thai rubber industry and its utilisation of renewable resources, focussing on the use of open source software in building supply chain models. By describing elements that the supply chain is composed of and relating this to Thailand's rubber industry, the authors then outline the construction of a Discrete Event Simulation (DES) model and use open source software to model renewable resources in this particular supply chain. Emphasis is placed on the way that modelling can aid the important decision-making required in the exploitation of natural resources. By taking a hands-on approach and offering a valuable guide for readers, this book not only appeals to academics in the fields of industrial engineering, operations, logistics and supply chain management, but also to practitioners, policy-makers and associations involved in the rubber industry.